No Guts, No Glory: Promoting Economic Independence of Brown Sugar Farmers Through Co-Operative - Puspasari Novita; Aryo Sudibyo Yudha (Holistica, 2019)
Banyumas regency is the largest producer of brown sugar in Indonesia. One location which produce brown sugar is in Ketanda Village. Unfortunately, most of brown sugar farmers have been trapped to bad middlemen for decades since they are lack of capital and market access. The farmers pay debt to middlemen with their sugar then the price is determined by the middleman. Moreover, middlemen buy brown sugar in much lower price than the market price. Both the buying price and the debt scheme determined by the middlemen are unfair to brown sugar farmers. This research used action research method. In the first step of action research, diagnosis, it was found that brown sugar farmers need an institution which can facilitate them to be free from middlemen, strengthen the farmers community, and also develop their business model. Therefore, the intervention made by gathering local actors and they committed to build a cooperative. There are two implications from this study. First, this study will enrich literature in cooperative as a social enterprise which has a main goal to manage social problem. Second, if successfully implemented, the cooperative model can be replicated in other regions to manage the same social problem, thus farmer’s economic independence will be achieved.